BarR, an Lrp‐type transcription factor in Sulfolobus acidocaldarius, regulates an aminotransferase gene in a β‐alanine responsive manner. Issue 3 (8th April 2014) - Liu, Han; Orell, Alvaro; Maes, Dominique; van, Marleen; Ann‐Christin, Lindås; Bernander, Rolf; Albers, Sonja‐Verena; Charlier, Daniel; Peeters, Eveline
Summary In archaea, nothing is known about the β‐alanine degradation pathway or its regulation. In this work, we identify and characterize BarR, a novel Lrp‐like transcription factor and the first one that has a non‐proteinogenic amino acid ligand. BarR is conserved in Sulfolobus acidocaldarius and Sulfolobus tokodaii and is located in a divergent operon with a gene predicted to encode β‐alanine aminotransferase. Deletion of barR resulted in a reduced exponential growth rate in the presence of β‐alanine. Furthermore, qRT‐PCR and promoter activity assays demonstrated that BarR activates the expression of the adjacent aminotransferase gene, but only upon β‐alanine supplementation. In contrast, auto‐activation proved to be β‐alanine independent. Heterologously produced BarR is an octamer in solution and forms a single complex by interacting with multiple sites in the 170 bp long intergenic region separating the divergently transcribed genes. In vitro, DNA binding is specifically responsive to β‐alanine and site‐mutant analyses indicated that β‐alanine directly interacts with the ligand‐binding pocket. Altogether, this work contributes to the growing body of evidence that in archaea, Lrp‐like transcription factors have physiological roles that go beyond the regulation of α‐amino acid metabolism.